Instrução explícita e diferenças individuais na aquisição de enunciados declarativos e interrogativos totais em Espanhol/L2 - Rodrigues, Rhanya Rafaella (2017)
The process of L2 acquisition tends to produce many controversies regarding the level of advanced performance of learners. Whereas some researchers attribute proficiency level to pedagogical practices worked up in the classroom, others affirm that individual differences, that is, specific characteristics of learners, interfere in this process (ORTIZ-PREUSS; SANZ, 2016). Nonetheless, Sanz (2005) suggests it should be investigated the relations between pedagogical conditions and individual differences of learners, in order to further explain the variability in final proficiency level of L2 adult learners. In addition, another prominent aspect is the lack of researches on acquisition of intonation in Spanish/L2. Based on that, in this research, we propose to observe the effects of explicit instruction in acquisition of total declaratory and interrogative utterances, which possess the most distinct intonational patterns between Portuguese and Spanish (DIAS, 2015). Intending to analyse possible interactions between effects of explicit instruction and IDs – Individual Differences (age, frequency of use, teaching experience and attention span capacity) in the acquisition of these utterances, we conducted a semi-experimental research of quantitative nature. The research participants were Brazilian learners of Spanish from intermediate-advanced level who were in the context of Spanish teaching graduation course and in the context of a language course center. These participants were divided into groups of four, considering: i) the context (graduation course or free course); and ii) the intervention (experimental or control). For obtaining the data, we used the following instruments: linguistic pre-test, linguistic post-test, questionnaire of linguistic background and proficiency, and test of attentional capacity (ANT). It should be noted that we used a free software, PRAAT, not only in the explicit instruction, as a way of evidencing the melodic contours produced by students, but also in the data analysis, to assigning scores to correct or incorrect utterance production. The participants of experimental groups were submitted to a period of explicit instruction about the target utterances in between pre-test and post-test. The results indicate that scores of participants of experimental groups enhanced after receiving explicit instruction, although differences in the analysis cannot be considered significant among the groups. Besides that, we observed the association between explicit instruction and age, frequency of use, general mastery of skills, having lived in Hispanic-speaking country and teaching experience. It was also verified that total interrogative utterances are more difficult for Brazilian learners of Spanish/L2 when compared to declaratory utterances. Lastly, the results point out that explicit instruction can contribute to the acquisition of this study’s target-utterances, however, we must consider that some IDs can maximize or supply the effects of explicit instruction. Keywords: Pedagogical Conditions. Individual Differences. Intonation. Spanish/L2. Effects of Explicit Instruction. Total Declaratory and Interrogative Utterances